2023
DOI: 10.1055/s-0043-1768204
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Free Flap Outcomes at a University Hospital versus County Hospital Setting for Head and Neck Reconstruction

Abstract: Introduction Patients at public county hospitals often have poorer access to healthcare with advanced disease on presentation. These factors, along with limited resources at county hospitals, may have an impact on outcomes for patients requiring complex head and neck reconstruction. Objective To delineate differences in the frequency of complications in two different care settings, a public county hospital and a private university hospital. Methods Retrospective review of otolaryngology pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A recent study from the Northeastern part of the country re‐emphasised the need for a trained team with adequate infrastructure to be able to deliver the best results 14 . A couple of studies have shown that free flaps can be performed safely in community hospitals with acceptable morbidity and mortality rates when compared to academic/teaching institutes (high‐volume centres) 15,16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study from the Northeastern part of the country re‐emphasised the need for a trained team with adequate infrastructure to be able to deliver the best results 14 . A couple of studies have shown that free flaps can be performed safely in community hospitals with acceptable morbidity and mortality rates when compared to academic/teaching institutes (high‐volume centres) 15,16 …”
Section: Discussionmentioning
confidence: 99%
“…14 A couple of studies have shown that free flaps can be performed safely in community hospitals with acceptable morbidity and mortality rates when compared to academic/teaching institutes (high-volume centres). 15,16 Potential barriers to free flap reconstruction can be classified into preoperative, intraoperative and postoperative (Table 4). One 17 This concept is important in a resource-constrained setting where judicious use of manpower can be rewarding for not only the residents but also the department or institution at large.…”
Section: Discussionmentioning
confidence: 99%